RETRACTED: Security indicators and standards for microprocessor centralization in “2x2” and “1x1” systems - Aripov Nazirjon; Mirzarakhmedov Zafar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001